Vetrne turbine - Biluš, lgnacijo; Kevorkijan, Luka; Lešnik, Luka (University of Maribor Press, 2025)
Wind Turbines. The publication addresses wind turbines. The first, introductory chapter presents the basic characteristics of energy supply in Slovenia and the potential for harnessing renewable resources, with an emphasis on wind energy. This is followed by a chapter on wind, explaining the origin of winds, wind characteristics with speed distribution, the influence of terrain and turbulence on wind energy. The chapter introduces a methodology for assessing wind availability and energy generation potential. The third chapter provides a mathematical formulation of the flow dynamics in conventional horizontal-axis wind turbines. Methods for evaluating the efficiency of energy exchange and fundamental procedures for designing wind turbine blades are presented. The fourth chapter discusses the environmental aspect of placing wind turbines in nature, including the impact of wind turbines on wildlife, landscape degradation due to visual impact, and noise caused by wind turbines.